DOI: 10.14264/uql.2019.545
|View full text |Cite
|
Sign up to set email alerts
|

On the design of small to medium scale radial inflow turbines for supercritical CO2 power cycles

Abstract: In rural Australia, concentrating solar power at sub 10 MWe scale is a candidate technology to displace current fossil fuel based technologies [1]. For concentrating solar power to be competitive for this application, coupling with an advanced power cycle is essential. A candidate is the supercritical CO 2 Brayton cycle, which is suitable for higher turbine inlet temperature operation, and has the potential to exceed the efficiency of the steam Rankine cycle. Furthermore, due to lower volumetric flow variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 79 publications
(282 reference statements)
0
1
0
Order By: Relevance
“…This method of providing power is prohibitively expensive and is a non-renewable source of energy. Recent research has shown that the use of sCO 2 power cycles in conjunction with a Concentrating Solar Thermal (CST) heat source, could provide a simple, efficient, renewable replacement to the diesel generators these communities currently rely on [8,23].…”
Section: Motivationmentioning
confidence: 99%
“…This method of providing power is prohibitively expensive and is a non-renewable source of energy. Recent research has shown that the use of sCO 2 power cycles in conjunction with a Concentrating Solar Thermal (CST) heat source, could provide a simple, efficient, renewable replacement to the diesel generators these communities currently rely on [8,23].…”
Section: Motivationmentioning
confidence: 99%